2008
DOI: 10.1016/j.chemgeo.2008.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement of ultramafic rocks into the continental crust monitored by light and other trace elements: An example from the Geisspfad body (Swiss-Italian Alps)

Abstract: In order to evaluate the influence of continental crustal rocks on trace element budgets of serpentinized peridotites incorporated into the continental crust, we have analyzed the chemical composition of whole rock samples and minerals of the Geisspfad ultramafic complex (Swiss-Italian Alps). This complex represents a relict oceanic succession composed of serpentinites, ophicarbonates and metabasic rocks, emplaced into crustal gneisses during Alpine collision. Following peak metamorphic amphibolite facies cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The dark grey-shaded area represents the global average of modern day sub-arc depths. Table 2 of Pelletier et al, 2008). Although such rocks experience significant dehydration over the 550-800˚C temperature range, relatively little CO 2 is lost and even the warmest of the P-T paths (Cascadia) results in only ~15% loss.…”
Section: Figurementioning
confidence: 97%
“…The dark grey-shaded area represents the global average of modern day sub-arc depths. Table 2 of Pelletier et al, 2008). Although such rocks experience significant dehydration over the 550-800˚C temperature range, relatively little CO 2 is lost and even the warmest of the P-T paths (Cascadia) results in only ~15% loss.…”
Section: Figurementioning
confidence: 97%
“…This indicates that chlo- Table 1. Oceanic chlorites from Scambelluri et al (2004) and Vils et al (2008), Geisspfad field after Pelletier et al (2008a). Only few other studies have so far determined Li and B in chlorite in ultramafic rocks.…”
Section: Behavior Of LI and B In Chlorite And Possible Dependence On mentioning
confidence: 97%
“…5). In-situ measurements of light elements in antigorite from metamorphic environments have been studied previously (Scambelluri et al, 2004;Marschall, 2005;Pelletier et al, 2008a). They showed that antigorite contains up to 39 lg/g B. Additionally, Scambelluri et al (2004) studied the B and Li composition in serpentine along the subduction path of ultramafic rocks, comparing samples from different localities with different P-T conditions.…”
Section: Line Missingmentioning
confidence: 98%
See 1 more Smart Citation
“…As B is abundant in seawater (4.6 lg g À1 , Quinby-Hunt and Turekian, 1983; Jean-Baptise et al, 1991) compared to depleted mantle (0.04 lg g À1 , Table 6), seawater-peridotite interaction should enrich the mantle in B. Various studies on dredged abyssal peridotites have confirmed this enrichment in serpentinite (Thompson and Melson, 1970;Bonatti et al, 1984;Spivack and Edmond, 1987;Boschi et al, 2008), and studies on alpine serpentinite have demonstrated a large variability of B contents in serpentine (Scambelluri et al, 2004;Pelletier et al, 2008).…”
mentioning
confidence: 98%